Proposals that set trends for another possible journalism in times of digital transformation and hostile environments - López-García, Xosé (Anuario ThinkEPI, 2023)
The search for other possible types of journalism has been present in the successive historical stages of the contemporary period since the birth of modern journalism. From the appearance of muckrakers to the new American journalism or precision journalism, there have been proposals that have enriched journalistic technique and contributed to the emergence of new journalistic roles. However, on many occasions "Adamism" emerges, and we face current challenges as if history had just begun and the past had left no trace. This brief paper examines the emergence of recent proposals that, in the digital scenario, raise the banner of impartiality to combat the lack of trust and low credibility that journalism offers to some sectors of the public. In addition to constructive journalism and solutions, as well as new transparency measures, the focus is on two new and recent publications: Factuel in France and The Messenger in the United States.